Erilaisten arviointimenetelmien yleisyys yläkoulun liikunnanopetuksessa ja yläkoulun liikunnanopettajien käsityksiä oppilasarvioinnista - Pirinen, Aleksi (2024)
The aim of this Master's thesis was to investigate the prevalence of different assessment methods in secondary school physical education (PE) and PE teachers' views regarding student assessment. According to previous research, PE teachers find interpreting the assessment criteria of the curriculum challenging when assigning summative grades, and at the same time, they have little experience with formative assessment, which is known for its learning supportive effect. Despite the benefits of formative assessment, its full potential has not yet been utilized in physical education. While teachers' views of assessment may reflect how they utilize assessment in their teaching. There is limited research on PE teachers' assessment views and assessment methods in Finland. The data for the study was collected as part of the Finnish Ministry of Education and Culture funded project "Development of Assessment Competence for Teachers of Physical and Health Education" (2018–2021). An online survey was e-mailed in 2019 to members of The Association of Physical and Health Educators in Finland. A total of 201 PE teachers responded to the survey. In this study, the sample was limited to physical education teachers teaching in secondary school (N=147, 78 % females). The data was analyzed using SPSS software. A hierarchical cluster analysis was conducted on the data to identify groups of teachers with differing assessment methods. The resulting groups were compared using cross-tabulation and the chi-square test based on gender, age, and variables measuring assessment views. Additionally, open-ended responses from teachers were subjected to a data-driven content analysis by categorizing similar responses into groups. After classification, the content analysis was continued by quantifying the data. Three distinct assessment profiles were identified among PE teachers: observers (n=96), formative assessors (n=31) and measurers (n=20). The groups did not differ by age. Women were more prevalent in the group of formative assessors, while men were more prevalent in the group of measurers, but the difference was not statistically significant (p=0,261). Formative assessors more often than others believed that assessment supports lesson planning (p<0,05). Good student assessment was most frequently described as diverse, encouraging, and fair. The findings of the study on the prevalence of observation as an assessment method confirm previous beliefs about its common use in physical education. In contrast, other assessment methods are relatively rare. There are also differences in how PE teachers emphasize various methods in physical education assessment. This can lead to a situation where students are in unequal positions, with some receiving more diverse assessments compared to others. The results of the study may help teachers better understand their own assessment practices and further diversify their assessment methods.